ENHANCEMENT STUDENTS’ CRITICAL THINKING SKILLS IN SCIENCE LEARNING THROUGH AN INDEPENDENT CURRICULUM - Annisa Nur Faujiah; Retno Triwoelandari; Ahmad Mulyadi Kosim (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
The low level of students' critical thinking skills is due to the fact that in the learning process students are not trained to think critically. This research has objectives including 1) knowing students' critical thinking skills in science lessons in grade 4, 2) knowing the application of the independent curriculum in science lessons in grade 4, and 3) knowing the inhibiting factors and supporting factors in improving students’ critical thinking skills in science lessons in grade 4. This research method is mixed methods with a concurrent triangulation model. The sample used, namely class 4B students with a total of 44 students. Quantitative data collection techniques were tests. Meanwhile, qualitative data collection techniques were observation, interviews, and documentation. The results obtained show that students' critical thinking skills after the implementation of the independent curriculum in science lessons in grade 4 have increased which is indicated by the increase in the average value of students' posttests worth 87,86. Based on the results of the paired sample t-test, the Sig. (2-tailed) 0,000 < 0,05. So, this shows that there are differences in students' critical thinking skills before and after the implementation of the independent curriculum in science lessons in grade 4 SDIT Baitussalam. Thus, it can be concluded that the implementation of an independent curriculum in science lessons can improve students' critical thinking skills.